DIVERSIFICATION IN POLYPTERIFORMES AND SPECIAL COMPARISON WITH THE LEPISOSTEIFORMES - Gayet M.; Meunier F.J.; Werner C. (My University, 2002)
Polypteriformes (or Cladistia) and Lepisosteiformes (or Ginglymodi) are two groups of freshwater fishes with ganoid scales. The earliest fossil records of these taxa are Albian (Lepisosteiformes) and Cenomanian (Polypteriformes) respectively in Gondwana; they are still extant. The 'first' appearance of the two groups in the fossil record (explosive in polypteriforms, gradual in lepisosteiforms) as well as their evolutionary mode (diversification/disparity or replacement) is described in detail. The lepisosteiforms appear to show a rapid radiation of post-Palaeozoic clades immediately upon origination, while the polypteriforms represent a counter-example with their sudden diversification and their sudden acquisition of several 'key innovations'.
Keywords: PALAEODIVERSIFICATION; POLYPTERIFORMES; LEPISOSTEIFORMES; PANGAEA; CRETACEOUS-RECENT; KEY INNOVATION; Cenomanian; Albian; Mesozoic::Cretaceous::Upper::Cenomanian; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Верхний::Сеноманский; Мезозой::Меловая::Нижний::Альбский